2004
DOI: 10.1152/physiolgenomics.00161.2004
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding mouse Muc19: cDNA, genomic organization and relationship to Smgc

Abstract: We previously demonstrated expression of full-length transcripts for sublingual mucin apoprotein, Muc19, of approximately 24 kb (Fallon MA, Latchney LR, Hand AR, Johar A, Denny PA, Georgel PT, Denny PC, and Culp DJ. Physiol Genomics 14: 95-106, 2003). We now describe the complete sequence and genomic organization of the apomucin encoded by 43 exons. Southern analyses indicate a central exon of approximately 18 kb containing 36 tandem repeats, each encoding 163 residues rich in serine and threonine. Full-length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…Although this antiserum was demonstrated previously to react with mucous cells and with high-molecular-mass glycoproteins from sublingual glands of mice (Culp et al 2004; Das et al Figure 2 Testing the specificity against gel-forming mucins of antiserum raised against purified rat Muc19. Homogenates from select mouse tissues that express Muc19 and/or other gel-forming mucins were subjected to SDS-PAGE (3-8% gradient gels).…”
Section: Immunohistochemical Localization Of Muc19mentioning
confidence: 98%
See 1 more Smart Citation
“…Although this antiserum was demonstrated previously to react with mucous cells and with high-molecular-mass glycoproteins from sublingual glands of mice (Culp et al 2004; Das et al Figure 2 Testing the specificity against gel-forming mucins of antiserum raised against purified rat Muc19. Homogenates from select mouse tissues that express Muc19 and/or other gel-forming mucins were subjected to SDS-PAGE (3-8% gradient gels).…”
Section: Immunohistochemical Localization Of Muc19mentioning
confidence: 98%
“…In the oral cavity, gel-forming mucins are secreted by the mucous cell phenotype found within mucous glands such as sublingual glands and multiple minor salivary glands. We use rodent sublingual glands as a model system to investigate mucous cell biology (Culp et al 1996;Luo et al 2001) and identified the gel-forming mucin, Muc19, as a secretory product of murine sublingual mucous cells (Fallon et al 2003;Culp et al 2004). Muc19 is a product of the gene Muc19/Smgc that contains 60 exons and spans ?105 kb of genomic sequence.…”
mentioning
confidence: 99%
“…The sequence of this protein perfectly matches mouse Muc19. Soon after, mouse Muc19 was completely sequenced and shown to have a cDNA length of 22,795 bp encoded by a total of 43 exons and spanning 106 kb of genomic DNA (12). It has a gel-forming mucin structure signal peptide, a large central exon with tandem repeats, VWC, VWD, and Cterminal CT domains.…”
mentioning
confidence: 99%
“…It has a gel-forming mucin structure signal peptide, a large central exon with tandem repeats, VWC, VWD, and Cterminal CT domains. Interestingly, the mouse Muc19 locus contains an additional transcript, submandibular gland protein C (Smgc) (12). Smgc is a major secretory product, and a marker of the type I (terminal tubule) cells of the neonatal rat and mouse submandibular gland, but its expression in the adult is present only in some intercalated duct cells (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation